Introduction: care aux Suds Quand le travail de care interroge les inégalités sociales - Borgeaud-Garciandía, Natacha; Guimarães, Nadya Araujo; Hirata, Helena (Revue internationale des études du développement, 2020)
Cet article introductif fait la lumière sur certains aspects de la production et de l’organisation du care dans des pays et régions dits « du Sud ». Partant d’une définition large du care, qui inclut ses dimensions sociales, politiques et éthiques, et des connaissances élaborées dans différents pays du Sud, trois thèmes centraux sont développés : le genre du care, les présences et carences de l’État, et les relations entre migrations et care. Ces thèmes sont sous-tendus par le rôle que jouent le care et sa distribution sociale sur les inégalités sociales et leur reproduction. L’article souligne à quel point nombre de travaux élaborés dans les Suds permettent d’interroger et d’enrichir la perspective du care et ses schémas explicatifs.
Keywords: approches et analyses; care; cours; justice sociale; migration; pol4022; premier cycle; rapports sociaux de sexe; ressource en ligne; santé; thématiques; travail; éthique; éthique du care

An affirmative look at a domesticity in crisis: Women, humour and domestic labour during the COVID-19 pandemic - Ceuterick, Maud (Feminist Media Studies, 2020)
Keywords: 2000 à aujourd'hui; 2010-2019; 2020-2029; approches et analyses; charge mentale; communication; covid-19; discipline; division sexuelle du travail; humour; médias sociaux; périodes historiques; rapports sociaux de sexe; ressource en ligne; thématiques; travail; travail domestique; émotions

Coronavirus, domestic labour and care: Gendered roles locked down - Craig, Lyn (Journal of Sociology, 2020)
The Covid-19 pandemic turned daily lives upside down. Lockdowns and physical distancing meant hundreds of thousands of people switched to working from home, significantly blurring the temporal and spatial boundaries between paid work, domestic labour and caring for others. This article explores gender relations, and the division of employment, domestic labour and care, drawing on early results from an online survey, Work and Care in the Time of Covid-19, carried out between 7 May and 4 June 2020.
Keywords: 2000 à aujourd'hui; 2020-2029; approches et analyses; australie; care; covid-19; discipline; division sexuelle du travail; océanie; pandémie; projet charge mentale; périodes historiques; rapports sociaux de sexe; régions géographiques; santé; sciences humaines; sociologie; soins aux enfants; thématiques; travail; travail de reproduction; travail invisible

Care, vulnérabilité et université : enjeux de la carrière professorale au féminin - Gaudet, Stéphanie; Marchand, Isabelle; Bourgeault, Ivy Lynn; Bujaki, Merridee (Éthiques de l’hospitalité, du don et du care : actualité, regards croisés, 2020)
Keywords: 2000 à aujourd'hui; amériques; approches et analyses; canada; care; division sexuelle du travail; professeures d'université; projet charge mentale; périodes historiques; rapports sociaux de sexe; régions géographiques; thématiques; travail

Guerrilla Girls: the art of behaving badly - Guerrilla Girls (Group of artists) (Chronicle Books, 2020)
Guerrilla Girls: The Art of Behaving Badly is the first book to catalog the entire career of the Guerrilla Girls from 1985 to present. The Guerrilla girls are a collective of political feminist artists who expose discrimination and corruption in art, film, politics, and pop culture all around the world. This book explores all their provocative street campaigns, unforgettable media appearances, and large-scale exhibitions. Captions by the Guerrilla Girls themselves contextualize the visuals. Explores their well-researched, intersectional takedown of the patriarchy In 1985, a group of masked feminist avengers'known as the Guerrilla Girls'papered downtown Manhattan with posters calling out the Museum of Modern Art for its lack of representation of female artists. They quickly became a global phenomenon, and the fearless activists have produced hundreds of posters, stickers, and billboards ever since. More than a monograph, this book is a call to arms. This career-spanning volume is published to coincide with their 35th anniversary. Perfect for artists, art lovers, feminists, fans of the Guerrilla Girls, students, and activists You'll love this book if you love books like Wall and Piece by Banksy, Why We March: Signs of Protest and Hope by Artisan, and Graffiti Women: Street Art from Five Continents by Nicholas Ganz.
Keywords: 1900-1999; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; amériques; approches et analyses; artivisme; arts; arts visuels et médiatiques; com5170; corps; cours; discipline; histoire de l'art; justice sociale; militance; patriarcat; premier cycle; périodes historiques; rapports sociaux de sexe; représentation des femme*; régions géographiques; sexisme; sofia; systèmes d'oppressions; thématiques; travail; états-unis

La charge mentale. Histoire d'une notion charnière (1976-2020) - Haicault, Monique (2020)
La notion est née au milieu des années 1970 dans le cadre d’un enseignement universitaire de sociologie et de recherches sur le travail des femmes et la division sexuée des activités identifiées dans toutes les sphères sociales, celle de la production des biens et celle de la production/reproduction des personnes.
Keywords: approches et analyses; capitalisme; charge mentale; discipline; histoire et politique; inégalités; projet charge mentale; rapports sociaux de sexe; sciences humaines; sociologie; systèmes d'oppressions; thématiques; travail; travail domestique

The care ceiling in higher education - Lynch, Kathleen; Ivancheva, Mariya; O'Flynn, Micheál; Keating, Kathryn; O'Connor, Monica (Irish Educational Studies, 2020)
This study examines the impact of managerialist policies on care relations in higher education. It is based on a study of 10 higher education institutions in Ireland. The paper shows that a care-free worker model is ingrained in systems of performance appraisal, especially for academics in universities, and increasingly in the Institutes of Technology, although it also impacts on support staff in other professions and occupations. It assumes a life of boundary-less working hours and unhindered mobility. The market-informed tools of performance appraisal, especially audits and metrics, cannot measure essential care work because care is a process and disposition, not a product. Because it is not countable caring becomes invisible as do the people who do it. The managerial ideology of 'work--life balance' merely operates as a mask that conceals how over-working is normalised. There is no legitimate language to name over-working for the structural problem that it is. When work organisations disregard care commitments outside of work, and even within it, these are then repackaged and fed back to women/carers as personal problems and failures. The idealised care-free worker model operates as a care ceiling over women particularly; it is taken as given, even natural.
Keywords: 2000 à aujourd'hui; approches et analyses; care; charge mentale; conciliation famille-travail; europe; famille; femmes universitaires*; irlande; patriarcat; politiques néolibérales; projet charge mentale; périodes historiques; rapports sociaux de sexe; rentabilité; régions géographiques; systèmes d'oppressions; thématiques; travail; travail du care

Comment la crise fait-elle ressortir les inégalités de genre ? - Plumauzille, Clyde (2020)
Aides-soignantes, caissières, aides à domicile… ce sont majoritairement des femmes qui se retrouvent en première ligne contre le virus. Comme le rappelle l’historienne Clyde Plumauzille dans ce podcast, ces inégalités ne sont pas nouvelles, la prise en charge d’autrui au sein du foyer ou dans la société étant historiquement dévolue aux femmes.
Keywords: 2000 à aujourd'hui; 2020-2029; approches et analyses; care; charge mentale; confinement; covid-19; histoire et politique; hétérosexisme; inégalités; projet charge mentale; périodes historiques; rapports sociaux de sexe; ressource en ligne; santé; sexisme; systèmes d'oppressions; thématiques; travail; travail domestique; violences; violences conjugales

Labor market outcomes of professional women with two children after the one‐child policy in China - Shen, Yang; Lai, Jiang (The Journal of Social Issues, 2020)
Since the implementation of the two‐child policy in China in 2016, it is unclear how professional women's labor force outcomes and family commitments have changed. Using interviews with 26 professional women with two children in Shanghai, we examined their work–life transitions and labor market outcomes. We found that the overarching constraints the interviewees faced included a lack of institutional childcare support, low paternal participation and increased physical and cognitive childcare labor. The women also experienced different constraining and enabling factors, leading to four types of labor market outcomes: enhancement, rebound, interruption and stagnation. Most of the interviewees who experienced career upward mobility after giving birth to a second child were urban singleton daughters who received tremendous parental support. Some participants experienced career interruption due to a lack of social support. The state should ensure family‐friendly work environments and promote paternal participation to reduce women's work–life conflict and address gender inequality.
Keywords: 2000 à aujourd'hui; 2010-2019; approches et analyses; asie; chine; conciliation famille-travail; famille; inégalités hommes-femmes; maternité; projet charge mentale; périodes historiques; rapports sociaux de sexe; régions géographiques; sexisme; soutien familial; systèmes d'oppressions; thématiques; travail; travail reproductif; travail rémunéré